2012
DOI: 10.3402/ijch.v71i0.18642
|View full text |Cite
|
Sign up to set email alerts
|

Alaska Native people's perceptions, understandings, and expectations for research involving biological specimens

Abstract: ObjectivesMembers of racially and ethnically diverse groups have been persistently underrepresented in biomedical research in general, possibly due to mistrust with the medical and research community. This article describes the perceptions, understandings, and expectations of Alaska Native people about research involving the collection and storage of biological specimens.Study designStratified focus groups.MethodsTwenty-nine focus groups with Alaska Native people (n = 178) were held in 14 locations using a sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 15 publications
(17 reference statements)
4
88
0
Order By: Relevance
“…Hiratsuka, Brown, Hoeft, and Dillard [10] explained that “A clear and extensive process of informed consent and continued improvements in sharing results may enhance the transparency of research intent, conduct, and use of obtained results among Alaska Native people.” It is important to Native people to know what their blood or tissue is used for and how the clinical trial is going to help their community. It is also important for these communities to be aware of historical occurrences related to biospecimen research and what to look for.…”
Section: Background and Significancementioning
confidence: 99%
“…Hiratsuka, Brown, Hoeft, and Dillard [10] explained that “A clear and extensive process of informed consent and continued improvements in sharing results may enhance the transparency of research intent, conduct, and use of obtained results among Alaska Native people.” It is important to Native people to know what their blood or tissue is used for and how the clinical trial is going to help their community. It is also important for these communities to be aware of historical occurrences related to biospecimen research and what to look for.…”
Section: Background and Significancementioning
confidence: 99%
“…Particular genetic variants of CYP2A6, CYP2B6, CHRNA5-A3-B4, CHRNB2, CHRNA5, CHRNA4 as well as nico tine metabolic ratio, a genetically informed biomarker, have been found to predict successful smoking cessation and response to pharmacotherapy (e.g., nicotine replacement therapy, varenicline, bupropion) [15][16][17][18]20,21]. AI/AN people have been historically underrepresented in medical research and may be less likely to benefit from current pharmacogenetic research and recommendations [19,[22][23][24]. A pharmacogenetic study among the Confederated Salish and Kootenai tribes in Montana found strikingly different allele frequencies in CYP450 genes, which account for a majority of drug Perceptions of pharmacogenetic research to guide tobacco cessation by patients, providers and leaders in a tribal healthcare setting Jaedon P Avey* [19].…”
mentioning
confidence: 99%
“…A history of unethical research conduct in AI/AN communities has negatively affected attitudes toward pharmacogenetic testing [23][24][25]. Examples of research misconduct include the Barrow alcohol study and the experiences of the Nuu-chah-nulth peoples of British Columbia and the Havasupai Tribe of Arizona with genetic research [26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…2). Hiratsuka et al (2012) have noted, for example, that AN participants considered proper respect for participants to be of paramount importance; respect should be shown through appropriate care of samples; communication about dates of destruction; and respectful, non-cavalier destruction of samples.…”
Section: Alaska Area Specimen Bank (Aasb)mentioning
confidence: 99%
“…It highlights, for example, that both samples and the data derived from those samples should be dealt with according to both tribal preferences and reciprocal relationships between researchers and the tribe. The code is also useful for thinking about how tribal communities, either alone or collectively, may create biobanks and other large data repositories similar to the Alaska Area Specimen Bank, which will be discussed below (Hiratsuka, Brown, Hoeft, & Dillard, 2012;Hoeyer, 2008).…”
mentioning
confidence: 99%